Anterior Knee Pain and Knee Functional Scores Following Common Approaches to Tibial Shaft Fractures - Sarthak Parikh, DO; Laurel Marsh, BS; Mateao Anderson, BS; Jeremy Scott, DO; Amar Patel, DO; Christopher Hendrix, MD; Keivan Abtahi, DO (JBJS Open Access)
Background:. Tibial shaft fractures are common, causing substantial morbidity. Intramedullary nailing offers advantages but often leads to anterior knee pain and functional issues. Methods:. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we conducted a systematic review on outcomes for different surgical approaches—suprapatellar (SP), infrapatellar (IP), medial parapatellar (MPP), and lateral parapatellar (LPP). Searches across Ovid, Embase, and PubMed identified studies from 2000 to 2023, including retrospective and prospective studies, randomized controlled trials, and case series on anterior knee pain and functional outcomes postsurgery. Bias was assessed using Cochrane's RoB2. Results:. Of 27 studies, 8 were noncomparative (3 SP, 3 IP, 1 MPP, 1 LPP), showing varied anterior knee pain and function outcomes. Comparative studies (12 SP vs. IP, 5 MPP vs. IP) indicated better patient-reported outcomes for SP over IP in anterior knee pain and knee function. Comparative data for MPP and LPP remain limited. Overall RoB was low. Conclusion:. SP has better patient-reported outcomes and lower anterior knee pain than IP. MPP and LPP approaches are promising but lack robust comparative data. Further large, prospective trials are needed to clarify optimal approaches for tibial shaft fractures. Level of Evidence:. Level III. See Instructions for Authors for a complete description of levels of evidence.